PP115 Patient And Public Involvement In Health Technology Assessment: Update Of A Systematic Review. (2017) - Tantchou, Mylène; Gagnon, Marie-Pierre; Poder, Thomas
Abstract : INTRODUCTION: There is a general consensus on the need to involve patients and the public in Health Technology Assessment (HTA) but questions remain about the best strategies for involving them into HTA structures and activities. The aim of this study was to update a systematic review (published in 2011) on patient and public engagement in HTA. METHODS: We searched papers published between January 2009 (end of the initial search) and November 2016 in eight databases and HTA journals using specific search strategies. We identified other publications through citation tracking, Internet search engines, HTA agencies websites, and discussion with experts in the field. Studies in English or French were included if they met the following criteria: (i) qualitative, quantitative or mixed-methods study; (ii) describing patients or public involvement; and (iii) in the HTA field. We extracted information using a pre-established grid including: characteristics of studies, type of activities for involving patients or public, effects on decisions, and factors facilitating or limiting involvement. RESULTS: We identified a total of 4, 762 new publications from the main search strategy. Among them, twenty-eight articles (reporting on twenty-three studies) met the inclusion criteria, whereas seventeen articles were included in the previous systematic review. Research designs are qualitative (18/23), quantitative (3/23) or mixed (2/23). Two main strategies for involving patients and public are generally described. The first is when public representatives participate directly in decision-making processes (participation) and the second is when patient or public input is sought to inform decisions (consultation or indirect participation). CONCLUSIONS: The number of studies on patient and public involvement in HTA has increased in recent years. Findings from this update are mainly consistent with those of the previous systematic review. However, studies are still needed to assess the effectiveness of different strategies for involving patients and the public in HTA.